Multi-approach study, digitization and dissemination of a Bronze-Age engraved cup found in Filo Braccio, Filicudi (Aeolian Islands, Italy) - Dario Giuffrida; Maria Clara Martinelli; Francesco Armetta; Maria Luisa Saladino; Rosina Celeste Ponterio (Virtual Archaeology Review)
Highlights: